Blood group and protein polymorphism in the Finnish native cattle populations - Kantanen, Juha; Ojala, Matti (Agricultural and Food Science, 1994)
Nine blood group loci and five polymorphic protein loci were investigated in the native East-, North- and West-Finnish cattle populations. The studied East-, North and West-Finnish cattle populations comprised 74, 55 and 121 individuals, respectively. According to the average degree of heterozygosity, East-Finnish cattle had the highest genetic variation and North-Finnish cattle the lowest. Within the loci investigated, the East- and North-Finnish cattle populations, which are threatened by extinction, did not lack genetic diversity. The genetic distances between West and North-Finnish cattle calculated by the Nei’s (1972) standard method ranged from 0.019 to 0.052 in three partly different locus groups and between East- and North-Finnish cattle from 0.034 to 0.046. The distances between East- and West- Finnish cattle were 0.030 in all cases. According to these results. East-, West- and North-Finnish cattle could be regarded as three different native breeds.